Halal certification with the self declare scheme perspective maqashid syariah al-syatibi - Bella, Alif Mujiyana Eka (Universitas Airlangga, 2024)
Muslim consumers are very concerned about the halalness of a product that is in accordance with Islamic law standards and product safety that is in accordance with health standards. So that the government increases the competitiveness of halal products in Indonesia, one of which is through halal certification with a self-declared scheme which can be easily accessed by business actors. This research aims to examine the halal certification of self declared schemes in the perspective of Al-Syatibi maqashid sharia. This research is a type of qualitative library research (literature review) conducted by collecting data and information from various sources contained in the library. The results of this study indicate that halal certification with a self-declaration scheme is a primary need (dharuriyyat need) which is oriented towards safeguarding 5 aspects of benefit, namely safeguarding religion, soul, mind, offspring, and property. Keywords: Halal Certification, Self Declare, Maqashid Sharia, Al-Syatibi